Sistem Pendukung Keputusan Rekomendasi Calon Ketua BEM Pada Perguruan Tinggi Menggunakan Metode Weighted Product (WP) dan MOORA - Syahputra, Irwan; Zalukhu, Anzas Ibezato; Hulu, Adil Priman Hati; Sartika, Dewi; Suhardiansyah, Suhardiansyah (Bulletin of Computer Science Research, 2026)
The BEM Chairperson is the highest position in an intra-campus organization elected by students. The process of selecting the BEM chairperson begins with a selection and choice based on several specific criteria that have different assessment weights. To determine the decision-making process, a decision support system (DSS) is one of the tools in solving this problem. Weight Product (WP) and MOORA are methods in SPK that are widely used to resolve decision-making that has many criteria and ranking systems. This study compares the WP and MOORA methods in selecting BEM chairperson candidates. Based on the calculation results, it is found that both methods can produce a sequence of BEM chairperson candidates. The stages of completing the WP and MOORA methods are determining the decision criteria, determining the weight of each criterion, determining alternatives and their values ??for each criterion, creating a decision matrix, normalizing the decision matrix, calculating the preference value for each alternative, sorting the largest value as a decision recommendation. Based on the results of the calculations for both methods, we can compare that the MOORA method, based on the Recommendation Assessment for the Election of Student Executive Board Chairperson at Budidarma University, Medan, selected alternative A1, Muhammad Aldi, S.Kom, with an optimization value of 0.4572. However, using the WP method, the selection of alternative A1, Muhammad Aldi, with a preference value of 0.193116, was selected as BEM Chairperson.